Setting health research priorities using the CHNRI method: VII. A review of the first 50 applications of the CHNRI method - Rudan, Igor (J Glob Health, 2017)
BACKGROUND: Several recent reviews of the methods used to set research priorities have identified the CHNRI method (acronym derived from the “Child Health and Nutrition Research Initiative”) as an approach that clearly became popular and widely used over the past decade. In this paper we review the first 50 examples of application of the CHNRI method, published between 2007 and 2016, and summarize the most important messages that emerged from those experiences. METHODS: We conducted a literature review to identify the first 50 examples of application of the CHNRI method in chronological order. We searched Google Scholar, PubMed and so–called grey literature. RESULTS: Initially, between 2007 and 2011, the CHNRI method was mainly used for setting research priorities to address global child health issues, although the first cases of application outside this field (eg, mental health, disabilities and zoonoses) were also recorded. Since 2012 the CHNRI method was used more widely, expanding into the topics such as adolescent health, dementia, national health policy and education. The majority of the exercises were focused on issues that were only relevant to low– and middle–income countries, and national–level applications are on the rise. The first CHNRI–based articles adhered to the five recommended priority–setting criteria, but by 2016 more than two–thirds of all conducted exercises departed from recommendations, modifying the CHNRI method to suit each particular exercise. This was done not only by changing the number of criteria used, but also by introducing some entirely new criteria (eg, “low cost”, “sustainability”, “acceptability”, “feasibility”, “relevance” and others). CONCLUSIONS: The popularity of the CHNRI method in setting health research priorities can be attributed to several key conceptual advances that have addressed common concerns. The method is systematic in nature, offering an acceptable framework for handling many research questions. It is also transparent and replicable, because it clearly defines the context and priority–setting criteria. It is democratic, as it relies on “crowd–sourcing”. It is inclusive, fostering “ownership” of the results by ensuring that various groups invest in the process. It is very flexible and adjustable to many different contexts and needs. Finally, it is simple and relatively inexpensive to conduct, which we believe is one of the main reasons for its uptake by many groups globally, particularly those in low– and middle–income countries.